Pengaruh Kompensasi, Kompetensi dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Kesehatan Provinsi Sumatera Selatan - Salam, Prima; Djazuli, Abid; Choiriyah, Choiriyah (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
The pupose of this study to determine the effect of compensation, competence and work environment on employee performance of health service of south Sumatera Province. Associative research is the methodology employed. Utilizing a random selection technique and the Isaac and Michael formulas received from 100 respondents, the study population consisted of 156 employees of health service of south Sumatera Province. Using SPSS 25 Program. Based on the results of the study, it is known that compensation and competence have a significant effect on employee performance, the work environment has no significant effect on employee performance partially. Meanwhile, the variables of compensation, competence and work environment have a significant effect on the performance of health service of south Sumatera Province.